Implementasi Algoritma Merkle Hellman untuk Keamanan Database - Simanjuntak, Magdalena; Pasaribu, Tioria; Rahmadilla, Semiati (MEANS (Media Informasi Analisa dan Sistem), 2019)
The development of information technology today has a huge impact, namely the issue of security and confidentiality of data. One solution that can be used to guarantee the confidentiality and security of information is cryptography. By using cryptography, a data can be secured through the decryption and encryption process. Security issues and database confidentiality are the most important aspects of an information system. One mechanism to improve database security is to use asymmetric algorithms such as the Merkle Hellmen algorithm. Merkle Hellman is one of the crypto systems that uses the key type of asymmetry. In the Merkle Hellman system, the keys used are 2 different keys, namely the public key and the secret key. Encryption generates ciphertext and decryption produces a plaintext for securing databases that want to be kept confidential. The advantages of this Merkle Hellman algorithm is that there is no need for confidentiality in the key distribution process. From the results of experiments that have been done with this application, the encrypted database becomes a form of message that cannot be understood (ciphertext), but after the decryption process is done, the database is successfully returned to its original form (plaintext) that can be understood